ROLE OF SCHOOL MANAGEMENT TEAMS IN MAINTAINING LEARNER DISCIPLINE IN KING CETSHWAYO DISTRICT USING INTEGRATED MANAGEMENT APPROACH - Khanyile, Hlengiwe G; Kapuaja, Ingrid S; Mhlongo, Hlengiwe R; Mpuangnan, Kofi N. (Education Administration Study Program, School of Postgraduate Studies, Universitas Riau, 2024)
This study explored the role of School Management Teams (SMTs) in using an integrated management approach to maintain learner discipline in King Cetshwayo District. A qualitative research method was employed in this study while data were collected data six SMT members by using semi-structured interview schedules. The participants were selected through a purposive sampling technique from schools in King Cetshwayo District. The collected data were analysed by following a thematic approach. The findings revealed significant challenges faced by School Management Teams (SMTs), indicating a lack of adequate training in handling disciplinary issues. Additionally, schools struggling with insufficient resources, such as counsellors and materials, found it difficult to implement effective disciplinary measures. Collaborative decision-making emerged as a key strategy within the Integrated Management Approach (IMA) for maintaining learner discipline in schools in the King Cetshwayo District. Based on the findings, regular team meetings were recommended for discussing and refining discipline policies grounded on comprehensive data insights. This can foster a collaborative and inclusive school environment.